Characterization of LiFePO₄ Nanostructures Synthesized by Solvothermal Method - Nguyen, Thi My Anh; Doan, Luong Vu; Nguyen, Thai Hoa; Le, My Loan Phung; Nguyen, Ba Tai; La, Thi Hang; Nguyen, Ngoc Trung; Nguyen, Nhi Tru (Old Journal, 2017)
In this work, we have synthesized LiFePO₄ particles with the size around 200 nm by solvothermal method. The crystalline LiFePO₄ was synthesized from LiOH.H₂O, FeSO₄.7H₂O and H₃PO₄ precursors, using ethylene glycol and water as solvents. Ascorbic acid was added to the solution to prevent oxidation of Fe²⁺ to Fe³⁺. The structure was characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM). Carbon black is determined to reduce the phase structure of Fe³⁺ remaining in the LiFePO₄ composition into Fe²⁺ after the annealing step. The LiFePO₄ particles were also mixed with EC 600JD carbon black and followed by the annealing at 550 oC for composite formation. Their electrochemical properties were determined by cyclic voltammetry (CV) and galvanostatic cycling with potential limit (GCPL).